Clinical practitioners' perception of the dimensions of patient safety culture in a government hospital: A one‐sample correlational survey. Issue 23 (5th September 2019) - Alenezi, Atallah; Pandaan, Ramon Perley M.; Almazan, Joseph U.; Pandaan, Isabelita N.; Casison, Franklyn S.; Cruz, Jonas Preposi
Abstract: Aims and objectives: To assess the perceptions of clinical practitioners regarding the different dimensions of patient safety culture in their hospital and examine the work‐related predictors of patient safety culture perceptions. Background: Patient safety is seen as a progressively critical focus in healthcare areas worldwide. Saudi Arabia aims to improve healthcare quality by providing access to healthcare for its increasing population. Hence, constantly assessing the patient safety culture of healthcare facilities in the country is imperative. Design: One‐sample correlational survey design. Methods: The Hospital Survey of Patients' Safety Culture was used to survey the total population sample of 181 healthcare practitioners in a Saudi hospital from December 2018–January 2019. Strengths and weaknesses on PS culture were identified as perceived by the clinical practitioners. Regression analysis was performed to identify the work‐related predictors of patient safety culture perceptions. The study followed the STROBE guideline. Results: Nine of the 12 dimensions measured were identified as patient safety culture weaknesses, including 'management support for patient safety' (49.2%), 'teamwork across unit' (44.2%), 'frequency of events reporting' (43.1%), 'communication openness' (41.3%), 'overall perception of patient safety' (38.7%), 'supervisor/manager expectations and actions promoting patient safety' (32.9%), 'staffing' (23.7%), 'hospital handoffs and transitions' (19.6%) and 'non‐punitive response to errors' (15.8%). None of the dimensions were identified as strengths by the respondents. Working hours per week and staff position were identified as significant predictors. Conclusions: The study underscores the urgent need to improve the patient safety culture of the hospital. Relevance to clinical practice: Hospital administrators should highlight initiatives on positive patient safety impact plan for clinical practitioners and patients, such as monitoring, reporting and strictly adhering to hospital activities that reduce the risks associated with exposure to medical care.